PEMBERDAYAAN KETERAMPILAN KOGNITIF MELALUI PENDEKATAN KONTEKSTUAL DALAM TATANAN PEMBELAJARAN KOOPERATIF TIPE TAI PADA SISWA SMPN 6 PEKANBARU - Ritonga, Zulfan (Jurnal Pilar Sains, 2008)
Class action research aims to describe your activities of teachers and students, learning management,cognitive skills of students. Research methods to the model Kemmis and Mc.Taggart, with thecontextual approach in the framework of cooperative learning TAI type. Implementation steps includeplanning, action, and reflection upon the actions carried out as many as two-cycle. Results of researchshowed the activities of teachers and students considered good, good management of your learning,and cognitive skills of students was increasing from one cycle and two cycles. As well as studentresponses to the implementation of learning is good. thus the application of the contextual approach inthe framework of cooperative TAI type can be one of the alternative learning materials in the basicfractions of seventh- four in SMPN 6 Pekanbaru.Key Words : Cognitive Skills, TAI